Preferensi Netizen Indonesia Terhadap Pariwisata: Apaakh Faktor Demografis Berpengaruh? - Suherlan, Herlan; Hidayah, Nurdin (Centre For Tourism Planning and Development, 2025)
This study aims to describe the preferences and relationships between preference attributes and demographic profiles of Indonesian netizens. This research uses a survey approach by distributing questionnaires through various online channels. The questionnaire was collected through various filters and screening questions, and a final sample of 1008 questionnaires were completed. The result indicated that Indonesian netizens prefer to avoid the risk in their tourism activities. This research shows that demographics affect the preferences and the influence of demographic factors on the sub-attributes of travel preferences varies widely. The demographic variable that most dominantly affects the sub-attributes of travel preferences is the gender variable, followed by the variable of origin, meanwhile, age and income variables were relatively less dominant in influencing the tourism preference sub-attributes.